Factors anticipated to customer experience / Muhammad Hanif Abdul Gafar...[et al.] - Abdul Gafar, Muhammad Hanif; Harudin, Syahmi; Mohd Ali, Nor Amira (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
In the past few years, customer experience had become more important for the hotel industry as a source of sustainable competitive advantage. In the meantime, little research has been done in the area of tourism and hospitality industry regarding the factors which lead to high quality of customer experience towards the hotel industry. Basically, the statistics from the Ministry of Tourism in Malaysia have shown that tourism activities in Malaysia keep increasing day-by-day and this opportunity will flow directly to the hotel which can generate high revenue by attracting international and local tourists for accommodations and other facilities provided by them. In fact, the hotel managements should examine the different aspects of their performance which can enhance the effectiveness and efficiency of their hotel service because customer will compare their provided services and facilities with other hotels with similar rates. As to ensure that customer experience helps hotels to gain customer trust, the hotels should examine their whole management whether it can create a good customer experience or not. Therefore, the aim of this research is to determine the relationship between peace of mind, moments of truth, and outcome focus towards customer experience. Simple random sampling technique was used and a self-administered questionnaire was distributed to the respondents (i.e hotel guest). The findings showed that peace of mind, moments of truth, and outcome focus have significant positive relationships towards customer experience. Hence, it implies that the hotel should make improvement to enhance their customer experience quality to drive customers’ satisfaction and loyalty.